GRAPHIC ANALYSIS OF EXPENSE. - Brush, Lauren F. (The Accounting Review, 1943)
Abstract In this article the author anticipates on the procedure of business management in the post-war era in the U.S. According to the author there are two points of view. One holds that there will be no problems for managers, the bureaucrats of government will have all the answers to all the questions, industrialists will look in the statute books rather than in their ledgers to determine their costs, and their merchandising plans will be based not upon market analysis but upon government directives. The alternative point of view is that the business administration will face additional complexities. Technology changes, changes in consumer's buying behavior and business organization changes can be expected. The author insists that in the light of knowledge that business management will, in the future, need more detailed information about those factors within the sphere of accounting, one shall do well to consider some of the recently developed tools which accountancy can supply. He suggests the consideration of graphic analysis of expense by using the break-even chart as an illustration of recently developed tools in accounting.